Integracija zemljiškega katastra s podatki prostorskih aktov - Rakuša, Martina (Geodetski vestnik, 2021)
Establishing a multi-purpose cadastre, especially in terms of upgrading cadastral contents with the various spatial data, such as land use, is a challenge in Slovenia and internationally. Land use strongly affects spatial planning, development, and management, so high-quality spatial integration of the land cadastre with spatial plans data is crucial for effective land management. In the first part of the article, we reviewed the literature and documents that prescribe guidelines for the development of the land cadastre; we use these guidelines as a basis for developing a proposed method of linking and harmonising the data of the land cadastre with the spatial plan data. Land use is specified in spatial plans, and we linked it to the graphical and attribute land cadastre data layer. WWe tested the method in Prekmurje with a high-quality cadastre. Selected study areas are the municipalities of Kramarovci and Nemčavci. As a result, we presented land use data directly in the land cadastre database, which requires simultaneous land use and cadastre maintenance. Based on the results for selected cadastral municipalities, we critically evaluated the proposed method.
Keywords: data connectivity; interoperability; land use; medopravilnost; multi-purpose cadastre; namenska raba; povezljivost podatkov; večnamenski kataster